2020
DOI: 10.2174/1570179416666191018145142
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-mediated Highly Efficient Synthesis of [1,2,4]triazolo/benzimidazoloquinazolinone Derivatives

Abstract: Objective: An efficient and catalyst-free procedure for the synthesis of [1,2,4]triazolo/benzimidazolo quinazolinones has been developed in 2,2,2-trifluoroethanol or deep eutectic solvent(DESs) as a clean reaction media. Methods: All of the obtained products are known compounds and identified by IR, 1HNMR,13CNMR, and melting points. Results: Various products were obtained in good to excellent yields under reaction conditions. Conclusion: We have efficiently developed a practical and catalyst-free approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Also, other studies have reported the synthesis of quinazolinone derivatives using deep eutectic solvents. 37,38 Referencing these studies demonstrates that the synthesis of quinazolinone derivatives in deep eutectic solvents has been explored in the literature. This highlights the signicance of the current study and its contribution to the existing knowledge in the eld.…”
Section: Introductionmentioning
confidence: 96%
“…Also, other studies have reported the synthesis of quinazolinone derivatives using deep eutectic solvents. 37,38 Referencing these studies demonstrates that the synthesis of quinazolinone derivatives in deep eutectic solvents has been explored in the literature. This highlights the signicance of the current study and its contribution to the existing knowledge in the eld.…”
Section: Introductionmentioning
confidence: 96%